2012
DOI: 10.1038/tpj.2012.8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis implicates the involvement of eight loci with response to tocilizumab for the treatment of rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is an immune-mediated inflammatory disease affecting the joints. A heterogeneous response to available therapies demonstrates the need to identify those patients likely to benefit from a particular therapy. Our objective was to identify genetic factors associated with response to tocilizumab, a humanized monoclonal antibody targeting the interleukin (IL)-6 receptor, recently approved for treating RA. We report the first genome-wide association study on the response to tocilizumab in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…Clinical, biochemical and genetic factors have been proposed as predictors of good response to TCZ in RA patients [10,11,[13][14][15][16]. Among clinical factors, the early administration of TCZ and an increased baseline DAS28 have shown better EULAR response and remission rates, although with conflicting results [10,14].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical, biochemical and genetic factors have been proposed as predictors of good response to TCZ in RA patients [10,11,[13][14][15][16]. Among clinical factors, the early administration of TCZ and an increased baseline DAS28 have shown better EULAR response and remission rates, although with conflicting results [10,14].…”
mentioning
confidence: 99%
“…Since TCZ administration in the clinical practice is relatively recent, the influence of genetics on response to TCZ is scarcely investigated. To date, only one genome-wide association study (GWAS) has tried to identify gene polymorphisms involved in the response to TCZ [13]. This GWAS, recently conducted in 1683 subjects with RA from six clinical studies, has identified several single nucleotide polymorphisms (SNP) in CD69 (rs11052877), GALNT18 (rs4910008), CLEC2D…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of 31 risk loci in seropositive RA, a very strong genetic risk factor in HLA-DRB1, and the group of alleles referred to as the shared epitope demonstrate that RA has a strong but complex genetic etiology. As a result, a genetic approach to the identification of biomarkers of response has been taken as a candidate and genome-wide level for anti-TNF (14) and tocilizumab (18,19) interventions. While associations that may ultimately lead to a greater insight into the molecular etiology of RA have been established, the predictive capability so far has been insufficient to have meaningful clinical application.…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…While associations that may ultimately lead to a greater insight into the molecular etiology of RA have been established, the predictive capability so far has been insufficient to have meaningful clinical application. Indeed, 2 studies by Wang et al (18,19) reported that each polymorphism identified in a genome-wide association study accounted for Ͻ2% of the variance observed with a change in Disease Activity Score in 28 joints (DAS28) response to tocilizumab, while no significant association of polymorphisms of the target IL-6 receptor and its cognate ligand IL-6 was associated with change in DAS28 response, following correction for multiple testing. Baseline serum IL-6 levels also provided little discrimination between responders and nonresponders, indicating that the prevalence of the therapeutic target was not clinically useful, despite having been previously proposed as "low-hanging fruit" (20).…”
Section: Significance and Innovationsmentioning
confidence: 99%